Atrazine removal using chitin-cl-poly(acrylamide-co-itaconic acid) nanohydrogel: Isotherms and pH responsive nature. (1st August 2020) - Sharma, Gaurav; Thakur, Bharti; Kumar, Amit; Sharma, Shweta; Naushad, Mu.; Stadler, Florian J.
Graphical abstract: Highlights: Atrazine removal using chitin based nanohydrogel- adsorption & desorption. Chitin- cl -poly(acrylamide-co-itaconic acid) - microwave synthesis. Results shows the maximum adsorption capacity of 204.08 mg/g. Chitin- cl -poly(acrylamide-co-itaconic acid) nanohydrogel - pH responsive nature. Abstract: Removal of commonly used pesticide, atrazine was examined by employing chitin based nanohydrogel. Chitin- cl -poly (acrylamide-co-itaconic acid) nanohydrogel was synthesized by microwave method. Dissolution of chitin was done by freezing thawing method in NaOH/urea solution. The morphology and functional characteristics were confirmed by FTIR, XRD, SEM, TGA, TEM, and EDX techniques. Maximum swelling capacity, isotherm study, kinetics, adsorption and desorption of atrazine pesticide were evaluated in this study. Maximum adsorption capacity of designed nanohydrogel was found to be 204.08 mg/g. Langmuir and pseudo- second order models were determined to be applicable for explaining the undertaken adsorption process. Neutral pH was found to be favorable for maximum adsorption. In addition, results have specified the pH responsive nature of nanohydrogel for controlled release of atrazine.